Analisis Penggunaan Sosial Media Marketing Dalam Meningkatkan Volume Penjualan Kue Home Industri Di Dapoer Zainab - Putri Yanuari Buaya; Emanuel Zebua; Idarni harefa; Eduar baene (Visi Sosial Humaniora, 2024)
This study is a descriptive research with a qualitative approach aimed at evaluating the use of social media marketing to increase sales volume at Dapoer Zainab, a home industry in Gunungsitoli City founded in 2020 by Regina Nababan. Data were collected through in-depth interviews with two key informants: the business owner, Mrs. Regina Nababan, and employee, Mrs. Swasti Idawati Lase. The results indicate that Dapoer Zainab currently relies on product photos as their main content strategy. However, this content has been less effective in capturing customer attention due to a lack of variety and creativity. Labor limitations have led to inconsistencies in content scheduling and the use of social media advertising features. The findings suggest that despite efforts in content creation, results have not been optimal in increasing engagement and sales volume. It is recommended to introduce new content types such as videos and customer testimonials, and to improve creativity and consistency in content scheduling to enhance marketing effectiveness. Implementing these recommendations is expected to help Dapoer Zainab achieve better growth and significantly increase sales.